Simulation of blueberry production in Lambayeque, Peru: An agent-based approach - Reyna-González, Julissa Elizabeth; Falcon, Andy Williams Chamoli; Huiman, Luis Vladimir Urrelo; Pozo, Marco Alberto Suárez; Vilca, Yamileé Melissa Cáceres (Edelweiss Applied Science and Technology, 2024)
This study presents an agent-based simulation to analyze and optimize blueberry production in Lambayeque, Peru. Using data [1]and various academic sources, a model was developed on the NetLogo platform. This model simulates the interactions between climatic, agronomic and logistical factors that affect the production and export of blueberries. The results suggest that the implementation of advanced technologies and optimized agricultural practices can significantly improve the efficiency and competitiveness of Peruvian producers in the global market. Simulation offers a valuable tool for making informed decisions in the agro-export sector.